2008
DOI: 10.1038/nprot.2008.156
|View full text |Cite
|
Sign up to set email alerts
|

SPIDER image processing for single-particle reconstruction of biological macromolecules from electron micrographs

Abstract: This protocol describes the reconstruction of biological molecules from the electron micrographs of single particles. Computation here is performed using the image-processing software SPIDER and can be managed using a graphical user interface, termed the SPIDER Reconstruction Engine. Two approaches are described to obtain an initial reconstruction: random-conical tilt and common lines. Once an existing model is available, reference-based alignment can be used, a procedure that can be iterated. Also described i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
393
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 453 publications
(398 citation statements)
references
References 35 publications
2
393
0
Order By: Relevance
“…Image processing was carried out on a Linux cluster. EMAN software 17 was used for particle selection; CTFFIND 18 for contrast transfer function (CTF) determination, BSOFT 19 for the CTF correction; Imagic 20 for multivariate statistical analysis and classification; Spider 21,22 for multireference alignment, projection matching (PM) and 3D reconstruction; hsearch and himpose programs from the IHRSR package 23,24 for symmetry search and imposition; URO 25 and its graphical version VEDA http://mem.ibs.fr/VEDA, for crystal structure fitting; Pymol 26 and Chimera 27 for visualization. Supplementary Fig.…”
Section: Discussionmentioning
confidence: 99%
“…Image processing was carried out on a Linux cluster. EMAN software 17 was used for particle selection; CTFFIND 18 for contrast transfer function (CTF) determination, BSOFT 19 for the CTF correction; Imagic 20 for multivariate statistical analysis and classification; Spider 21,22 for multireference alignment, projection matching (PM) and 3D reconstruction; hsearch and himpose programs from the IHRSR package 23,24 for symmetry search and imposition; URO 25 and its graphical version VEDA http://mem.ibs.fr/VEDA, for crystal structure fitting; Pymol 26 and Chimera 27 for visualization. Supplementary Fig.…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, we decided to not pursue reconstruction of the "curved" receptor, because the biological significance of this configuration is currently unknown. The remaining classes (1-5) were sufficiently homogeneous and populated to allow 3D reconstruction by the random conical tilt method (20).…”
Section: Resultsmentioning
confidence: 99%
“…To extend this analysis, we manually selected 12,612 particle tilt pairs (at 0°and 55°) using WEB (20). Reference-free alignment and classification of the untilted views into 100 classes with IMAGIC-5 (21) showed that most receptor dimers adopted a preferred orientation, lying sideways on the carbon support film, and exposing the distinctive twofold symmetry previously seen in the crystal structure of SCF-induced dimeric KIT extracellular complex (Fig.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…were manually selected using the program boxer from the EMAN2 package (22); extracted into boxes of 500 by 500 pixels (full phage, coarsened by 2), 200 by 200 pixels (capsid), 100 by 100 pixels (connector), 80 by 80 pixels (tail), or 100 by 100 pixels (baseplate); and combined into the five different data sets (Table 1). The data sets were pretreated using the SPIDER package (23) and submitted to maximum likelihood (ML) classification and alignment (24) using the Xmipp package (25). The initial models were built to form a visually selected class average representing a side view imposing the corresponding symmetry (C6 for the full phage, tail, and baseplate; C12 for the connector; and icosahedral for the capsid).…”
Section: Methodsmentioning
confidence: 99%